Natural antibiofilm agents and the need for antibiofilm drug leads - Adnan Hazniza, Seidel Veronique, Tucker Nicholas P (Universiti Pendidikan Sultan Idris, 2017)
Natural antibiofilm agents and the need for antibiofilm drug leads by Adnan Hazniza, Seidel Veronique, Tucker Nicholas P,